Effectiveness of Understanding Relations between Community, Home, and School for Future Educators - Peralta, Claudia; Galaviz, Sonia (GIST – Education and Learning Research Journal, 2013)
As educators committed to preparing teachers to teach effectively across differences and in ways that actively resist perpetuating injustices, we have found  that designing opportunities that take teachers  into the children’s community  is the best way to learn about the cultural wealth existing in homes and to understand the importance of including parents in the education of their children. College students from a graduate program at a public institution were asked to engage in community, neighborhood and home visits to reflect on their understanding of the relationship among  community, home, and schools. As a result of these interactions, the students came to a new and deeper understanding of the importance of bringing together communities, schools, and homes to create an optimum environment for student success.